Properties of mixed lipid monolayers assembled on hydrophobic surfaces through vesicle adsorption - Park, Jin-Won (Langmuir : the ACS journal of surfaces and colloids, 2006)
Supported lipid films are becoming increasingly important tools for the study of membrane protein function because of the availability of high-sensitivity surface analytical and patterning techniques. In this study, we have characterized the physical chemical properties of lipid films assembled on hydrophobic surfaces through the spontaneous adsorption of large unilamellar lipid vesicles composed of dioleoylphosphatidylglycerol (DOPG) and dioleoylphosphatidylcholine (DOPC). The density of the lipid films was measured with surface plasmon resonance spectroscopy as the lipid composition of the vesicles and ionic concentration were varied. As expected, monolayer films were formed, but the density of the monolayers was found to be weakly dependent on the lipid composition of the vesicles and strongly dependent on the ionic concentration of the solution in contact with the monolayer. Atomic force microscopy (AFM) images of the lipid films indicate that they are composed of a homogeneous monolayer. Surface force measurements were used to determine the surface charge and DOPG density of the monolayers. The DOPG content of the films was found to be weakly dependent on the DOPG composition of the vesicles and strongly dependent on the salt concentration of the environment. A model has been developed to describe the behavior of the lipid composition of the films in terms of the hydrophobic, electrostatic, and steric forces acting on the lipid monolayer on the hydrophobic surface